Maintenance therapy in hormone receptor-positive and human epidermal growth factor receptor 2-positive metastatic breast cancer: a real-world multicenter retrospective study - Bao, Shengnan; Chen, Jia; Yin, Yongmei (Frontiers in Oncology, 2026)
IntroductionThe optimal choice of maintenance therapy after standard first-line treatment for hormone receptor (HR)-and human epidermal growth factor receptor 2 (HER2)-positive metastatic breast cancer (MBC) remains uncertain. Therefore, we evaluated the clinical value of trastuzumab combined with endocrine therapy (ET group) compared with trastuzumab combined with chemotherapy (CT group) as maintenance therapy in patients with HR+/HER2+ MBC.MethodsThe clinical data of 117 patients with HR+/HER2+ MBC who received trastuzumab combined with endocrine therapy or chemotherapy as maintenance therapy at three hospitals in China between January 2012 and October 2022 were retrospectively analyzed. The primary endpoint was progression-free survival (PFS). To construct a nomogram, a Cox regression model was used for both the univariate and multivariate analyses. The predictive ability and accuracy of the nomogram were assessed using the concordance index and calibration curves.ResultsHerein, 73 and 44 patients were assigned to the ET and CT groups, respectively. PFS was significantly longer in the ET group than the CT group (median PFS, 10.8 months vs. 7.2 months; adjusted hazard ratio, 0.68; 95% confidence interval, 0.46 to 0.99]; p=0.039). Based on the results of the multivariate analysis, a nomogram was established, which enabled visual risk prediction and demonstrated acceptable predictive ability.DiscussionMaintenance therapy using trastuzumab combined with endocrine therapy following standard first-line treatment may improve the survival and safety of patients with HR+/HER2+ MBC.